First, we need to define k because it is a missing zero;

Knowing that a(2)=0;

a(t)=(t-k)(t-3)(t-6)(t+3)

a(2)=(2-k)(2-3)(2-6)(2+3)=0

(2-k)(-1)(-4)(5)=0

(2-k)(20)=0

(2-k)=0/20

2-k=0

2=k

Therefore, the final equation is a(t)=(t-2)(t-3)(3-6)(t+3) with the zeros being (2, 3, 6, -3)

Hope I helped :)

So, your answer to this problem is

**x = **<span>

**±3√6i**</span>

**Answer:**

+4

**Step-by-step explanation:**

**Answer:**

The Answer is

**Step-by-step explanation:**

Let me draw this triangle for you as you haven't drawn the triangle.

To find the side SR , you have shown that

ΔPST ~(is similar to)ΔPRQ [AA]

As, you know when triangles are similar their sides are proportional.

So,

You can solve this question using other way also

As, ST║RQ

then ⇒ [ if in a triangle a line is parallel to a side

intersecting the other two sides in distinct points then the ratio of the segments where the line segment intersects the other two sides are same.]

So you would do 5*2x +5*-8 +15=-15

Then simplify so it would be 10x + -40 + 15 = -15

Then add -40 and 15 together

Then it would be 10x + -25 = -15

Then add 25 to -25 and -15

So it would be 10x = 10

And then divide 10 from 10 with would be 1 so x = 1